Creating New Battery Configuration Associated with the Functions of Primary and Rechargeable Lithium Metal Batteries. Issue 14 (4th March 2021) - Chen, Hao; Cao, Zhenjiang; Gu, Jianan; Cui, Yanglansen; Zhang, Yongzheng; Zhao, Zehua; Cheng, Zongju; Zhao, Qi; Li, Bin; Yang, Shubin
Abstract: Although the primary lithium/fluorinated graphite battery has a high energy density of 3725 Wh kg −1, its complete irreversibility based on a conversion reaction between Li and fluorinated graphite hampers wide applications in rechargeable systems. Here, a new rechargeable three‐electrode battery configuration involving lithium, fluorinated graphite, and sulfur electrodes is developed, in which the initial middle‐fluorinated graphite cathode can be electrochemically transformed into a hybrid lithium anode, showing a low overpotential (12 mV), long cycle life (2000 h) and good deep stripping/plating features. This rechargeable battery delivers a high gravimetric energy density of 507.7 Wh kg −1 on the basis of the total mass of the three‐electrode materials. Moreover, the excessive consumption of lithium in the system can be in situ replenished, further lengthening the lifespan. Abstract : A rechargeable three‐electrode battery configuration involving in lithium, fluorinated graphite and sulfur electrodes is developed, in which the initial middle‐fluorinated graphite cathodes can be electrochemically transformed into hybrid lithium anodes. This rechargeable battery configuration delivers a high energy density up to 507.7 Wh kg ‐1 and good cycle stability. Moreover, the excessive consumption of lithium can be in situ replenished, lengthening the lifespan.